1953
DOI: 10.1128/jb.66.1.10-16.1953
|View full text |Cite
|
Sign up to set email alerts
|

A Glucose-6-Phosphate Dehydrogenase in Leuconostoc Mesenteroides

Abstract: Glucose fermentation by Leuconostoc me8enteroides has been shown to proceed via a mechanism which differs from the classical Embden-Meyerhof glycolytic scheme. DeMoss, Bard, and Gunsalus (1951) found no evidence in cell-free extracts of this organism for the key enzyme aldolae but showed that cellular suspensions ferment glucose to equimolar quantities of ethanol, C02, and lactate as obligatory products. The diphosphopyridine nucleotide linked dehydrogenases for D-3-phosphoglyceraldehyde, D(-) lactic acid, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1957
1957
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Glucose 6-phosphate dehydrogenase (G6PD) (E.C. 1.1.1.49) from Leuconostoc mesenteroides is one such enzyme (De Moss et al, 1953). Our investigation of this enzyme has been motivated by a desire to understand the mechanism whereby the enzyme selects NAD or NADP for catalysis and the protein structural basis of this dual coenzyme specificity.Earlier work (summarized by Levy [1989]) demonstrated that the NAD-and NADP-linked reactions catalyzed by L. mesenteroides G6PD proceed via different kinetic mechanisms, and that this difference appears to be the basis upon which the enzyme selects the appropriate coenzyme.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Glucose 6-phosphate dehydrogenase (G6PD) (E.C. 1.1.1.49) from Leuconostoc mesenteroides is one such enzyme (De Moss et al, 1953). Our investigation of this enzyme has been motivated by a desire to understand the mechanism whereby the enzyme selects NAD or NADP for catalysis and the protein structural basis of this dual coenzyme specificity.Earlier work (summarized by Levy [1989]) demonstrated that the NAD-and NADP-linked reactions catalyzed by L. mesenteroides G6PD proceed via different kinetic mechanisms, and that this difference appears to be the basis upon which the enzyme selects the appropriate coenzyme.…”
mentioning
confidence: 95%
“…Glucose 6-phosphate dehydrogenase (G6PD) (E.C. 1.1.1.49) from Leuconostoc mesenteroides is one such enzyme (De Moss et al, 1953). Our investigation of this enzyme has been motivated by a desire to understand the mechanism whereby the enzyme selects NAD or NADP for catalysis and the protein structural basis of this dual coenzyme specificity.…”
mentioning
confidence: 99%
“…Liver alanine aminotransferase (ALT) and aspartate aminotransferase (AST) was assayed as described by Wootton () with 0.2 M DL‐alanine and 2 mM L‐ketoglutarate and 0.2 M DL‐aspartic acid and 20 mM L‐ketoglutarate as the substrate, respectively. Glucose‐6‐phosphate dehydrogenase (G6PDH) activity in liver tissues was analysed by the method of De Moss, Gunsalus, and Bard (). The reaction mixture comprised 1.5 ml of 0.1 M Tris buffer (pH 7.8), 0.2 ml of 2.7 mM NADP, 0.1 ml of tissue homogenate, 1 ml of distilled water and 0.1 ml of 0.02 M glucose‐6‐phosphate (G6P) and absorbance was recorded at 340 nm at the 15 s interval for 3 min against distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The third group of the enzyme can react approximately equally well with NAD and NADP. This class includes the enzyme from a number of bacterial strains such as Leuconostoc mesenteroides (Demoss et al, 1953;Olive et al, 1971), Pseudomonas aeruginosa (Ju-Fang et al, 1998), Pseudomonas W6 (Reuter et al, 1990), Streptomyces aureofaciens (Haghighi et al, 2005), Methylomonas M15 (Steinbach et al, 1978). In dog liver G6PD NADP was replaced by d-NADP (Deamino NADP).…”
Section: Substrate and Coenzyme Specificitymentioning
confidence: 99%